Pertimbangan Hakim Dalam Menjatuhkan Pidana Terhadap Pelaku Tindak Pidana Pembunuhan Berencana - Deti Rahmawati; I Ketut Siregig; Zainudin Hasan (Widya Yuridika, 2021)
The purpose of this study was to determine the consideration of the judge in criminal sentencing againts the planned murder , determine the criminal responbility againts the planned murder in decision number 172/Pid.B/2020/PN Gns in Gunung sugih first instance court. The method use a normative juridical and empirical juridical approach. The type of data used is secondary data and primary data. Collecting data through library research and field research. Analysis of the data used is qualitative juridical. field research in Gunung sugih first instance court and lampung tengah attorney office. The result of the research shows that the Panel of Judges in its previous considerations took into account the prosecutor's indictment, witness statements, defendant's testimony, evidence, other evidence such as letters and instructions, as well as prosecutors' demands. The judge's deliberations contained burdensome matters as well as lightening in deciding the criminal against the accused. Other judges' considerations come from the humanitarian side. And the Panel of Judges sentenced him to 20 (twenty) years in prison.